IMF Staff Papers, Volume 54, No. 4. (IMF Staff Papers; IMF Staff Papers ;, 2008)
In this issue, authors from the IMF and from Argentine institutions team up to review how different banks behaved and were hurt during the country's crisis. Atsushi Iimi looks at how countries can escape from the resource curse in a comparative analysis that focuses on Botswana. John Cady and Jesus Gonzalez-Garcia examine the relationship between exchange rate volatility and the transparency of reserves. The issue also includes a comprehensive index of all Volume 54 papers by author, title, subject, and JEL classification.